2006
DOI: 10.1051/0004-6361:20052807
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositions and plasma parameters of planetary nebulae with Wolf-Rayet and wels type central stars

Abstract: Aims. Chemical compositions and other properties of planetary nebulae around central stars of spectral types [WC], [WO], and wels are compared with those of "normal" central stars, in order to clarify the evolutionary status of each type and their interrelation. Methods. We use plasma diagnostics to derive from optical spectra the plasma parameters and chemical compositions of 48 planetary nebulae. We also reanalyze the published spectra of a sample of 167 non-WR PN. The results as well as the observational da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
36
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 30 publications
16
36
1
2
Order By: Relevance
“…In the case of NGC 2867, our derived O/H ratio from CELs (3.8 × 10 −4 ) is somewhat lower than previous estimates in the literature: O/H = 6.0 × 10 −4 , 4.4 × 10 −4 and 4.3 × 10 −4 by Kingsburgh & Barlow (1994), Girard et al (2007) and Peña et al (1998), respectively. Peña et al (1998) pointed out that the high O/H ratio obtained by Kingsburgh & Barlow (1994) There is a broad distribution in the O/H values reported in the literature for PB 6.…”
Section: Comparison With Other Abundance Determinationscontrasting
confidence: 87%
See 3 more Smart Citations
“…In the case of NGC 2867, our derived O/H ratio from CELs (3.8 × 10 −4 ) is somewhat lower than previous estimates in the literature: O/H = 6.0 × 10 −4 , 4.4 × 10 −4 and 4.3 × 10 −4 by Kingsburgh & Barlow (1994), Girard et al (2007) and Peña et al (1998), respectively. Peña et al (1998) pointed out that the high O/H ratio obtained by Kingsburgh & Barlow (1994) There is a broad distribution in the O/H values reported in the literature for PB 6.…”
Section: Comparison With Other Abundance Determinationscontrasting
confidence: 87%
“…Comparing the ratio of the other elements with respect to oxygen, the agreement with these authors is excellent, except in the case of S/O, for which we have found a ratio 3 times larger than that found by Girard et al (2007). The O/H ratio derived from ORLs is much higher than solar (by almost a factor of 3).…”
Section: Comparison With Other Abundance Determinationssupporting
confidence: 84%
See 2 more Smart Citations
“…They also had to contain enough objects to allow us to assess their quality and internal integrity in a way that is similar to our own data presented here. These requirements were met by the following papers: de Freitas Pacheco et al (1992), Kingsburgh & Barlow (1994), Cuisinier et al (1996Cuisinier et al ( , 2000, Ratag et al (1997), Escudero & Costa (2001), Kwitter & Henry (2001), Peña et al (2001), Milingo et al (2002), Escudero et al (2004), Exter et al (2004), Górny et al (2004Górny et al ( , 2009, Girard et al (2007), Wang & Liu (2007), Cavichia et al (2010), Henry et al (2010), and Górny (2014). In short, we found useful optical spectroscopic literature data for 76, 30, and nine Galactic PNe in the lists by Stanghellini et al (2012), Perea-Calderón et al (2009), andGutenkunst et al (2008), respectively.…”
Section: Nebular Abundances From Literature Datamentioning
confidence: 99%